Efficacy of hyperbaric oxygen therapy in treating fibromyalgia linked to childhood trauma after late-onset and over a decade of symptoms: a case report - Mouzayan Ginzarly; Sherif Khairy; Zemer Wang; Umair Qureshi; Raghda Zaitoun; Shai Efrati (Journal of Medical Case Reports)
Abstract Background Fibromyalgia syndrome is a chronic pain disorder characterized by central sensitization and neuroinflammation. Conventional treatments primarily focus on symptom management but often fail to address the underlying dysfunction. Hyperbaric oxygen therapy has emerged as a promising approach that promotes neuroplasticity and may provide symptom relief. Case presentation We present the case of a 62-year-old North African female patient with treatment-resistant fibromyalgia and a history of childhood trauma who underwent 60 hyperbaric oxygen therapy sessions over 12 weeks (90 min at 2.0 atmospheres absolute). Baseline and posttreatment assessments included clinical evaluations (Fibromyalgia Impact Questionnaire Revised, widespread pain index, and symptom severity scale), neurocognitive testing, magnetic resonance imaging–diffusion tensor imaging, single-photon emission computed tomography imaging, and functional mobility tests. Following hyperbaric oxygen therapy, the patient reported substantial pain reduction (Fibromyalgia Impact Questionnaire Revised score decreased from 60.5 to 44; Fibromyalgia Diagnostic Criteria Questionnaire score decreased from 16 to 12). Computerized cognitive assessments revealed a 10% improvement in global cognitive function and a 26.9% increase in attention. Medication use was also reduced, with the discontinuation of pregabalin (Lyrica) and a 50% reduction in duloxetine (Cymbalta) dosage. Additionally, physical function improved, with walking speed increasing from 3.2 to 4.5 km/h and notable gains in balance and coordination. Corresponding to the clinical improvements, the brain imaging demonstrated increased perfusion on single-photon emission computed tomography and enhanced white matter integrity on magnetic resonance imaging–diffusion tensor imaging. Conclusion Hyperbaric oxygen therapy promotes neuroplasticity, resulting in significant clinical improvements in fibromyalgia syndrome, including pain reduction, enhanced cognitive function, and improved physical mobility. These findings highlight the potential of hyperbaric oxygen therapy as a therapeutic strategy targeting the core pathophysiology of fibromyalgia syndrome rather than solely managing symptoms.